(untitled) (Perner’s Contacts, 2010)
This paper discusses the possibility of use of two traffic assignment approachesto solve the problem of identification of vulnerable links. The first method is basedon Dial’s algorithm originally used to solve the stochastic traffic assignmentproblem. The second method calculates the costs experienced by all the networkusers according to the user equilibrium assignment (before and after particular linkfailure). This approach is not new but not commonly used because of its highcomputation complexity; this complexity can be considerably reduced usingthe subnetwork approach. There are proposed some new modificationsof the subnetwork approach which could reduce the complexity of the original idea.